2014
DOI: 10.4054/demres.2014.30.20
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying policy tradeoffs to support aging populations

Abstract: BACKGROUNDCoping with aging populations is a challenge for most developed countries. Supporting non-working adults can create an unsustainable burden on those working. One way of dealing with this is to raise the normal pension age, but this has proven unpopular. A complementary approach is to raise the average labor force participation rate. These policies are generally more politically palatable because they often remove barriers, allowing people who would like to work to do so. OBJECTIVETo conceptualize and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…Increases in the official normal ages for eligibility for state pensions have been planned in most OECD countries, and rationalised on the basis of forecast longevity gains (Australian Treasury 2013OECD 2013;UK Department for Work and Pensions 2013;Scherbov et al 2014). Indeed in some countries, such as Germany, Finland, and Portugal, pension benefit levels have been linked to life expectancy (Stoeldraijer et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Increases in the official normal ages for eligibility for state pensions have been planned in most OECD countries, and rationalised on the basis of forecast longevity gains (Australian Treasury 2013OECD 2013;UK Department for Work and Pensions 2013;Scherbov et al 2014). Indeed in some countries, such as Germany, Finland, and Portugal, pension benefit levels have been linked to life expectancy (Stoeldraijer et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Mortality change, related changes to health, and population ageing more broadly can also affect population size and the size of the labour force, growth rate, productivity, income, consumption and saving, government expenditure, and taxation revenue. All of these may in turn affect labour force participation rate (Auerbach and Kotlikoff 1992;Lee et al , 2001Lee et al , 2014McDonald and Kippen 2000;Kelley and Schmidt 2005;Skirbekk 2008; Lee and Mason 2010;Williamson 2013;Parr and Guest Prskawetz and Sambt 2014;Scherbov et al 2014). Because of the extensive data and modelling requirements that would be involved in the consideration of such effects, they were not taken into account in our study.…”
Section: Introductionmentioning
confidence: 89%
“…The implications of increased ageing include pressures for increased public expenditure on pensions, social security, health and aged care, and reductions in the size of the economically active population relative to that of the aged population. Increases in the official normal ages for eligibility for state pension have been planned in most Organisation for Economic Co-operation and Development (OECD) countries, and justified by forecast longevity gains (Australian Treasury 2009Treasury , 2014United Kingdom Department of Work and Pensions 2013;OECD 2014;Scherbov et al 2014). The study reported in this paper considered the prospects for future mortality change across an extensive range of developed countries and the implications of the change for economic support ratios.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of population aging has been recognized for many years by demographers, economists, and others and there has been a variety of approaches used to assess the possible role of immigration as an instrument to offset its negative effects. Attention has been given by various authors to population size and age distribution (Bijak et al, 2007(Bijak et al, , 2008Loichinger, 2015;Mamolo and Scherbov, 2009;United Nations, 2013), the overall level of economic activity and standard of living (Barrell, Fitzgerald, and Riley, 2010;Denton and Spencer, 2000;Kahanec and Zimmerman, 2008;Lee and Mason, 2011;Masson and Tryon, 1990), the fiscal positions of governments (Auerbach and Oreopoulos, 2000;Bonin et al, 2000;Dustmann et al, 2010;Lee and Miller, 2000;Rowthorn, 2008;Storesletten, 2000), and more particularly to the sustainability of publicly financed pension and health care programs (Alonso, 2009;Anderson and Hussey, 2000;Scherbov et al, 2014). Others have been concerned with possible undesirable effects of immigration on the incomes and employment of the domestic population (Borjas, 2003;Brücker and Jahn, 2009;Card, 2009Card, , 2012Dustmann et al, 2005Dustmann et al, , 2013Friedberg and Hunt, 1995;Jean and Jiménez, 2010;Longhi et al, 2005;Okkerse, 2008;Ottaviano and Peri, 2007;Peri, 2012;Ruhs and Vargas-Silva, 2014) and on the distribution of government transfer payments as between immigrants and non-immigrants (Blanchflower and Shadforth, 2009;Kerr and Kerr, 2011).…”
Section: Introductionmentioning
confidence: 99%